Sarcoidosis after Alemtuzumab therapy: Is Alemtuzumab posing a threat to its patients? - Nizamani, Misbah (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Sarcoidosis is a multi-system disorder characterized by the formation of non-caseating granulomas. It is a disorder of unknown etiology. Interferon-induced sarcoidosis is a well-known phenomenon. However, in the past few years, few cases have come forward in which after treatment with a monoclonal antibody, Alemtuzumab, patients developed sarcoidosis. This antibody targets the pan-lymphocyte CD52 antigen found on both human lymphoid and myeloid cells and is used in the treatment of Relapsing Remitting Multiple Sclerosis, leukemia, etc. Patients, in these cases, after a few years of treatment developed sarcoidosis but fortunately responded well to the treatment, if needed.